1976
DOI: 10.1103/physrevlett.37.618
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Low-Temperature Lattice Anomaly in SrTiO3and KTaO3

Abstract: nent in the electronic wave function outside a solid surface. This feature is unique to INS among the electron spectroscopies used to determine surface electronic structure.Because the effective neutralization energy of the ion is ~ 2 eV less than the free-space value, 5 we can estimate the distance s m where neutralization occurs. Equating &E n = 2 eV to the principal interaction term, namely the image interaction (3.6 eV A)/s m , we obtain s m~ 1.8 A as the distance of the ion from the image plane. This simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[15][16][17][18][19][20][21] Recently, efforts have focused on the socalled ''quantum paraelectric state'' in which quantum fluctuations of the atomic positions suppress the FE transition and lead to a stabilized paraelectric state. [17][18][19][20]22,23 This hypothesis has received dramatic support from a recent experiment showing that isotopically exchanged SrTi 18 O 3 appears to become ferroelectric at 23 K, 24 suggesting that normal SrTi 16 O 3 must be very close indeed to the ferroelectric threshold.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Recently, efforts have focused on the socalled ''quantum paraelectric state'' in which quantum fluctuations of the atomic positions suppress the FE transition and lead to a stabilized paraelectric state. [17][18][19][20]22,23 This hypothesis has received dramatic support from a recent experiment showing that isotopically exchanged SrTi 18 O 3 appears to become ferroelectric at 23 K, 24 suggesting that normal SrTi 16 O 3 must be very close indeed to the ferroelectric threshold.…”
Section: Introductionmentioning
confidence: 99%
“…From a viewpoint of dielectrics, the C\h-distorted H2SQ molecule produces a large polarizability, but cannot show long-range ordering due to the quantum fluctuation of the proton-skeleton coupled motion. Therefore, the presently observed phenomenon may be interpreted in terms of the concept of quantum paraelectricity, which was originally introduced to interpret the anomalous dielectric properties for SrTiC^ and KTaC>3 [19,20] near 0 K. A similar proton-skeleton coupled motion may also play some role in the T-P phase diagrams for the hydrogen-bonded ionic crystals of KDP families [5,6], in which the PC>4 3~ tetrahedrons show temperature-dependent C2-type distortions [21], and large dielectric constants near 0 K in their pressureinduced PE phase [5].…”
mentioning
confidence: 99%
“…The emergence of a maximal capacitance is a feature that has been observed in other manganite junctions before 8, 9, and can be ascribed to SrTiO 3 . As reported, the dielectric properties of SrTiO 3 undergo an abnormal variation below ∼60 K 11, 12. It is interesting to note the reduction of the maximal capacitance in LCMO/LMO/STON, which could be a signature of an enhanced built‐in potential in depletion layer.…”
Section: Resultsmentioning
confidence: 53%
“…This behavior appears accompanying the dielectric anomaly of SrTiO 3 , and could be a signature of dielectric correlation between electric dipole moments. It has been suggested that the antiferroelectricity or quantum paraelectricity occurs in SrTiO 3 below ∼60 K 11, 12. The evolution of the frequency dependency of the capacitance with dc biases deserves special attention.…”
Section: Resultsmentioning
confidence: 99%